Selection of Cellulase and Xylanase-Producing Fungi for Rice Straw Digestion in Ruminants - Noolaong, J.; Kaewmanee, J.; Sukkaew, A. (Tropical Animal Science Journal, 2025)
The efficient degradation of lignocellulosic biomass is essential for sustainable bioenergy production and the enhancement of ruminant feed quality. This study aimed to isolate and characterize cellulase and xylanase-producing fungi from soil and decayed wood samples collected in the Hala-Bala Forest, Yala Province, Thailand, and to evaluate their potential for rice straw fermentation. A total of 15 fungal isolates were obtained through selective culturing and identified by internal transcribed spacer (ITS) region sequencing. The identified species included Trichoderma reesei, Aspergillus niger, Chaetomium globosum, Penicillium oxalicum, Fusarium oxysporum, Trichoderma viride, Aspergillus flavus, among others. Enzymatic activity was screened using plate assays with carboxymethyl cellulose (CMC) and xylan substrates. T. reesei demonstrated the highest enzymatic potential, with clear zones of 5.2 cm for cellulase and 6.8 cm for xylanase. Six top-performing strains (T. reesei, A. niger, F. oxysporum, A. flavus, C. globosum, and T. viride) were selected for rice straw fermentation trials using a completely randomized design. Fermentation quality was assessed through pH, lactic acid content, and organoleptic properties (color, odor, and texture). Results revealed that rice straw fermented with A. niger, A. flavus, and T. viride exhibited optimal pH, high lactic acid levels, and favorable physical characteristics. Additionally, chemical composition analysis showed that rice straw fermented with A. niger and T. viride had significantly higher crude protein content and improved fiber fractions (neutral detergent fiber, acid detergent fiber, cellulose, hemicellulose), indicating improved nutritional value for ruminants. These findings emphasize the possible use of indigenous fungal isolates for bioconversion of lignocellulosic biomass into value-added products for sustainable agriculture and energy applications.